The effectiveness of video counseling (vidcon) education on anxiety levels in 'fast-track' peri-operative care protocols in minor and major surgeries - Ulfani, Ritma; Wahyuni, Sri (JOURNAL OF Mental Health Concerns, 2026)
Background: Anxiety in patients with planned surgery, especially major surgery, is unavoidable. However, the role of medical personnel, particularly nurses, can provide stimulation to reduce anxiety. Approximately 80% of patients undergoing surgery report experiencing anxiety. Unresolved anxiety can lead to psychological problems and delays in scheduled surgeries, resulting in delayed treatment. Purpose: To analyze the effectiveness of video counseling education (Vidcon) on anxiety levels in pre-operative patients. Method: Experimental research (quasi-experimental) with a With Control Group Pretest Posttest Design with Purpusive sampling of 110 respondents (control: 55 and intervention: 55). Results: Most were aged 19-35 years, female gender, higher education did not work in minor surgery and did not have comorbidities. The pre-anxiety level with a mean of 18.2 and post with a mean of 12.7. There was a difference in anxiety levels before and after the intervention in the treatment group with a value of 0.000 and the control group p-value: 0.065. Conclusion: Effectiveness in providing Video Counseling education (Vidcon) on anxiety levels in pre-operative patients with acceleration in the basic with a p-value of 0.000. Keywords: Anxiety; Pre-Operation; Video Counseling (Vidcon) Education.